A Descriptive Approach to the Phenomenon of Suicide in Merida, Venezuela - Crespo, Freddy (2019)
The present study is a descriptive approximation to suicide in Merida, Venezuela, with the objective of exposing and alerting about the behavior of this phenomenon and its differentiated tendency with the rates of the other states of Venezuela in the period 1995-2012. Using a complementary methodology, the national suicide trend and its differentiation between the different states is exposed. Likewise, in-depth interviews were conducted with the relatives of the suicidal persons in the state. The results show that Merida's suicide rate behaves differently from the national trend and that of the other states, since it is the highest in the period under study. On the other hand, the interviews show a destructuring of the relationship between means and social goals due to the situation that the country is going through, which leads to the accumulation of tension of the individual. The main conclusion is that this situation is generating new morphologies for the expression of violent behavior, among which suicide is a very probable action.